2021
DOI: 10.1136/jitc-2020-002230
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of programmed death-ligand 1 protein expression between primary and metastatic lesions in patients with lung cancer

Abstract: Assessment of programmed cell death-ligand 1 (PD-L1) expression by immunohistochemistry (IHC) is the definite diagnostic test to guide treatment for patients with advanced-stage non-small cell lung cancer. Intratumoral heterogeneity and discrepancy of PD-L1 expression between primary and metastatic lesions may increase the risk of tumor misclassification. We performed a retrospective study of the Foundation Medicine, Inc clinical database on lung cancer cases that were evaluated for PD-L1 expression by IHC in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…PD-L1 expression is a biopsy-based biomarker, with the disadvantage that a small biopsy specimen does not capture the full extent of tumor heterogeneity of PD-L1 expression and is associated with a higher chance of a false negative test result [6-8 10]. In addition, substantial heterogeneity of PD-L1 expression can be observed within and between tumor lesions of the same patient [11]. As a consequence of this lack of a good predictive biomarker, the majority of patients with advanced stage NSCLC patients are treated with a PD-(L)1 checkpoint inhibitor, with or without chemotherapy [2 5].…”
Section: Introductionmentioning
confidence: 99%
“…PD-L1 expression is a biopsy-based biomarker, with the disadvantage that a small biopsy specimen does not capture the full extent of tumor heterogeneity of PD-L1 expression and is associated with a higher chance of a false negative test result [6-8 10]. In addition, substantial heterogeneity of PD-L1 expression can be observed within and between tumor lesions of the same patient [11]. As a consequence of this lack of a good predictive biomarker, the majority of patients with advanced stage NSCLC patients are treated with a PD-(L)1 checkpoint inhibitor, with or without chemotherapy [2 5].…”
Section: Introductionmentioning
confidence: 99%
“…there was heterogeneity of PD-L1 expression between NSCLC and BM in some patients, the PD-L1 expression between PT and BM is concordant in most patients [20,51,52]. There may be less heterogeneity in synchronous patients [20,53].…”
Section: Reviewmentioning
confidence: 94%
“…Inter-tumor and intra-tumor heterogeneity of PD-L1 expression, a wide variety of PD-L1 assays and cutoff values utilized to define PD-L1 positivity, and the effect of handling and storage of tumor tissue on PD-L1 analysis render it an imperfect biomarker (11,(49)(50)(51)(52). Studies have shown significant discordance in PD-L1 expression between lung biopsies and corresponding resected tumors, between primary and metastatic sites, and among different metastatic sites (53)(54)(55). Finally, SCLC remains an invincible enemy with only a limited success achieved with incorporation of currently available ICIs in the treatment paradigm, largely driven by an immunosuppressive tumor microenvironment (TME) (56).…”
Section: Challenges Facing Ici Therapy In Lung Cancermentioning
confidence: 99%